Elite Maize Lines Having Variability in Quality Parameters—A Valuable Starting Material for Grain Quality-Oriented Breeding Programs - Vojka Babić; Valentina Nikolić; Milosav Babić; Natalija Kravić; Jovan Pavlov; Sladjana Žilić; Zoran Čamdžija; Milomir Filipović (Agriculture)
Numerous factors, including genetic background, environmental conditions, agricultural practices, and postharvest management, affect maize grain quality. Six maize hybrids with common parental components were evaluated in micro- and production trials during five years, aiming at evaluating grain yield and grain quality traits and ascertaining the pattern of evaluated trait relationships based upon sources of variation (hybrid, year, and parental components). The parental effects were significant for the majority of analyzed quality traits, while the year effect was significant for all examined parameters. The PCAs indicated a considerable impact of the hybrids’ genetic makeup on physical parameters and kernel structure. The findings suggested the possibility of breeding simultaneously for higher protein and starch contents accompanied by a yield increase and higher protein and oil contents followed by a yield reduction. Multiple adverse interactions, which are inherently driven by the kernel structure, hamper the simultaneous breeding for higher oil and starch content. Significant quality parameter variation in the micro-trial was insufficient to provide improvement in grain quality obtained in the production trial. Although the existing variability of elite germplasm in quality parameters can be exploited, the introgression of new germplasm with high values of quality parameters per se is necessary for breeding focused on diverse applications.